Attracting Comments: Digital Engagement Metrics on Facebook and Financial Performance. Issue 1 (2nd January 2018) - Yoon, Gunwoo; Li, Cong; Ji, Yi (Grace); North, Michael; Hong, Cheng; Liu, Jiangmeng
Abstract : Many companies are now using social media such as Facebook for advertising and marketing purposes. To understand how using social media affects a company's business performance from a digital engagement perspective, this study examines how user comments on company Facebook posts influence company revenue. S&P 500 companies' revenue information in a five-year time span (from 2010 to 2015) is collected, and this information is matched to more than 24 million user comments directed at these companies' Facebook posts. The hypotheses are tested using static (fixed effects [FE] and random effects [RE]) as well as dynamic (generalized method of moments [GMM]) panel data analyses in econometric methods. The estimation results indicate that digital engagement volume, defined as the total number of Facebook comments a company received, has a significant and positive effect on revenue. In addition, digital engagement valence, defined as the average tone of Facebook comments directed toward a company, also has a significant and positive effect on revenue. Implications and directions for future research are discussed.